Star wars 3 : revenge of the Sith. - Lucas, George (Pasig City : Viva Video, 2005)
The STAR EARS saga is now complete on VCD with Episode III REVENGE OF THE SITH. Torn between loyalty to his mentor, Obi-Wan Kenobi, and the seductive powers of the Sith, Anakin Skywalker ultimately turns his back on the Jedi, thus completing his journey to the dark side and his transformation into Darth Vader. Experience the breathtaking scope of the final chapter in spectacular digital clarity and relive all the epic battles including the final climactic lightsaber duel between Anakin and Obi-Wan. Bring home this VCD and discover how Episode III connects the entire STAR WARS saga.